Bio-Attractant of termites bait from waste paper and extract Ocimum basilicum Linn against Subterranean Termites Coptotermes curvignathus Holmgren - Farah Diba; Palguna Wiranata; Nurhaida Nurhaida; Muhammad Dirhamsyah; Rudi Hartono (Masyarakat Peneliti Kayu Indonesia, 2022)
Termites were the most destroying wood organism and one of the methods for controlling termites and suppressing its population is the baiting system. One of the conditions in the baiting system method is that the bait must be able to attract termites. Mostly the attractant is made from an extract of the plant. This research aimed to evaluate the attractants of termites bait from waste paper and extract of basil leaf (Ocimum basilicum) against subterranean termites Coptotermes curvignathus Holmgren. Leaves of Ocimum basilicum extracted with maceration process with ethanol. After extraction, the yield was made into five concentration, consist of 2%, 4%, 6%, 8% and 10%. The waste paper was made into termite’s bait with a square bait with measure 2 cm long x 2 cm wide x 1 cm thick. The result of research showed that the average of termites mortality value was 18.79% - 97.58%. The highest termites mortality was achieve on 10% concentration of extract Ocimum basilicum. Its followed by the concentration 8% with mortality value 91.52%; concentration 6% with mortality value 78.18%; concentration 4% with mortality value 61.82% and concentration 2% with mortality value 51.52%. Meanwhile on control treatment the mortality value was 18.79%. The average of weight loss of termite’s bait was 3.41% - 8.36%. The highest weight loss was achieved on concentration 8% and this bait was more attractive to termites. Termite’s bait from waste paper and extract of Ocimum basilicum was attractant to subteranean termites Coptotermes curvignathus and the optimum concentration was 8%.